IL-17A blockade or deficiency does not affect progressive renal fibrosis following renal ischaemia reperfusion injury in mice. (2nd June 2017) - Thorenz, Anja; Völker, Nicole; Bräsen, Jan Hinrich; Chen, Rongjun; Jang, Mi-Sun; Rong, Song; Haller, Hermann; Kirsch, Torsten; Vieten, Gertrud; Klemann, Christian; Gueler, Faikah
Abstract: Objectives: IL-17A contributes to acute kidney injury and fibrosis. Therefore, we asked whether IL-17A deficiency or treatment with a IL-17A blocking antibody impacts severe renal ischaemia reperfusion injury (IRI) and the progression to chronic kidney disease (CKD). Methods: IL-17A-deficient and wild-type (WT) mice underwent transient unilateral renal pedicle clamping for 45 min to induce IRI and subsequent renal fibrosis. Furthermore, a neutralizing anti-IL-17A antibody (mAb) was injected into WT mice before induction of renal IRI intravenously. On days 1, 7 and 21, inflammation, fibrosis, leukocyte infiltration and pro-inflammatory and pro-fibrotic cytokine expression were assessed in kidneys using histology, qPCR and flow cytometry. Key findings: IL-17A was significantly increased after renal IRI in WT kidneys. Levels of pro-inflammatory (MCP-1) cytokine and pro-fibrotic (collagen 1α1, fibronectin) transcripts were similar in the experimental groups studied. IL-17A deficiency had no effect on renal T-cell influx or the number, inflammatory phenotype, or spatial distribution of macrophages. Similarly, administration of an IL-17A blocking antibody did not attenuate inflammation. Conclusions: Despite the effects of IL-17 in other inflammation models, neither genetic IL-17A deficiency nor treatment with an IL-17A blocking antibody attenuated IRI and progression to CKD. We conclude that in severe renal IRI IL-17A is not crucially involved in disease progression.